2010
DOI: 10.2134/jeq2009.0229
|View full text |Cite
|
Sign up to set email alerts
|

Acidity Decay of Above‐Drainage Underground Mines in West Virginia

Abstract: Acidity of water from abandoned underground mines decreases over time, and the rate of decrease can help formulate remediation approaches and treatment system designs. Th e objective of this study was to determine an overall acidity decay rate for above-drainage underground mines in northern West Virginia from a large data set of mines that were closed 50 to 70 yr ago. Water quality data were obtained from 30 Upper Freeport and 7 Pittsburgh coal seam mines in 1968, 1980, 2000, and 2006, and acidity decay curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…It is difficult to evaluate the role of specific reclamation activities in the restoration of Tom's Run because a variety of remediation efforts have been implemented, and because there is some evidence that over time AMD discharges will attenuate without abatement efforts as acid-forming minerals are depleted from exposed overburden. Studies have found significantly lower pollution loads after approximately 40 years in untreated watersheds (Wood et al, 1999), and a reduction in acidity at a rate of about 2% per year (Mack et al, 2010). Thus, it is possible then that the water quality improvements in Tom's Run are at least in part due to the natural depletion of exposed pyrite.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to evaluate the role of specific reclamation activities in the restoration of Tom's Run because a variety of remediation efforts have been implemented, and because there is some evidence that over time AMD discharges will attenuate without abatement efforts as acid-forming minerals are depleted from exposed overburden. Studies have found significantly lower pollution loads after approximately 40 years in untreated watersheds (Wood et al, 1999), and a reduction in acidity at a rate of about 2% per year (Mack et al, 2010). Thus, it is possible then that the water quality improvements in Tom's Run are at least in part due to the natural depletion of exposed pyrite.…”
Section: Discussionmentioning
confidence: 99%
“…Various analytical methods have been proposed for the quantification of the first flush from underground mines (Demchak et al, 2001;Frost, 1979;Gzyl and Banks, 2007;Mack et al, 2010). The approaches in these studies relied mainly on the contaminants' time dependent decay rates in mine water fitted with decay curves.…”
Section: Introduction and Previous Investigations On Mine Floodingmentioning
confidence: 99%
“…By extrapolation, the further course of the contaminants was then predicted. Mack et al (2010) report that most of the investigated underground mines had an annual contaminant decay rate of approximately two percent per annum. Additionally, Mack et al (2010) highlighted that due to changing hydrogeological conditions in the mines, the decay rates are likely to be dynamic with higher decay rates in the initial stages of the first flush, equilibrating to lower ones at later stages.…”
Section: Introduction and Previous Investigations On Mine Floodingmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in Demchak et al (2004), the type of underground mine (above-drainage versus below-drainage) is an important factor in the degree and rate of change in water chemistry over time and the prediction of future changes (Mack et al 2010).…”
Section: Introductionmentioning
confidence: 99%